ANALISIS KORELASI KECANDUAN HANDPHONE DENGAN INSOMNIA PADA REMAJA SMK SAAT MASA PANDEMI COVID-19 - Rohanah Riri; Ratumas Ratih P; Mila Febriana; Mella Yurian R.A (Jurnal Education and Development, 2023)
During adolescence, adolescents must be able to meet their physiological needs, one of which is the need for rest and sleep. With the Covid-19 pandemic, learning activities in both schools and institutions have replaced online learning methods using cellphones (HP). Not only for studying but teenagers also use it for social interaction and there are many interesting applications available on HP so that it can make teenagers become more intensely addicted to HP which can affect their sleep quality like insomnia. The purpose of this study was to determine the relationship between cellphone addiction and the incidence of insomnia in class X adolescents at SMK Taruna Terpadu 1 Bogor during the Covid-19 pandemic. The research method is a quantitative approach with a cross-sectional research design with a total population of 123 and a sample of 93 students. The sampling technique uses purposive sampling, uses primary data (questionnaire) with the analysis using the Spearman rank test. The results of the study showed that the value of r value = 0.000 <a = 0.05 It can be concluded that there is a significant relationship between cellphone addiction and the incidence of insomnia in class X adolescents at SMK Taruna Terpadu 1 Bogor during the Covid-19 pandemic. The correlation coefficient of +0.783 shows that the relationship between cell phone addiction and the incidence of insomnia is strong and has a unidirectional correlation. Suggestions from the results of this study are that students reduce cell phone use and improve sleep quality.